Dosing of Aminoglycosides To Rapidly Attain Pharmacodynamic Goals and Hasten Therapeutic Response by Using Individualized Pharmacokinetic Monitoring of Patients with Pneumonia Caused by Gram-Negative Organisms - Kashuba, A. D. M. (American Society for Microbiology, 1998)
Achieving a peak aminoglycoside concentration (C(max))/MIC of ≥10 within 48 h of initiation of therapy for pneumonia caused by gram-negative organisms results in a 90% probability of therapeutic response by day 7. Targeting an MIC of 1 μg/ml, empirical aminoglycoside loading doses of 348 (25th- to 75th-percentile range, 275 to 432) mg were calculated to obtain a C(max)/MIC of 10 in our patient population. Individualized pharmacokinetic monitoring coupled with MIC data should determine subsequent dosing regimens to minimize the potential for toxicity and maximize the probability of clinical response.